2008
DOI: 10.1111/j.1095-8312.2008.01053.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinal variation in developmental time and viability, and the response to thermal treatments in two species of Drosophila

Abstract: The present study first addressed the question of whether developmental time (DT) and viability (VT) vary clinally along latitudinal and altitudinal gradients in Drosophila buzzatii, an autochthonous specialist and the generalist invasive Drosophila melanogaster. Coincident and positive altitudinal clines across species and, direct and inverse latitudinal clines were observed for DT in D. melanogaster and D. buzzatii, respectively. Opposing latitudinal and altitudinal clines were detected for VT only in D. mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 54 publications
(53 reference statements)
2
47
0
1
Order By: Relevance
“…The associations between DT and altitude and thermal amplitude are congruent since daily mean thermal amplitude is likely to be more common in highland than in lowland sampling sites [8]. Further analysis comparing highland (after grouping localities situated above 1000 meters above sea level) and lowland (below 1000 meters above sea level) populations showed that DT in highland substitution lines was, on average, 12 hours longer.…”
Section: Discussionmentioning
confidence: 66%
“…The associations between DT and altitude and thermal amplitude are congruent since daily mean thermal amplitude is likely to be more common in highland than in lowland sampling sites [8]. Further analysis comparing highland (after grouping localities situated above 1000 meters above sea level) and lowland (below 1000 meters above sea level) populations showed that DT in highland substitution lines was, on average, 12 hours longer.…”
Section: Discussionmentioning
confidence: 66%
“…The type of GEI observed indicate that, if natural populations present analogous genetic variants, selection might favor different genotypes in environments with distinct temperatures contributing to maintain intra-specific genetic variability [38], [65]. Finally, this might help to explain the clinal patterns repeatedly observed in Drosophila for different traits, including the morphological ones [66][75]. This would occur through the process of genetic assimilation [76] which seems to be an appealing mechanism for body size evolution based on abundant evidence of GEIs for traits in general and body size in particular [77].…”
Section: Discussionmentioning
confidence: 89%
“…When ßuctuating temperature has been used in experiments, this usually involved only one variable treatment that was compared with constant temperature treatments. However, a number of recent studies have been conducted using two or more ßuctuating temperature regimes (Petavy et al 2001a,b;Schaefer and Ryan 2006;Ragland and Kingsolver 2007;Folguera et al 2008Folguera et al , 2009Folguera et al , 2011Ragland and Kingsolver 2008;Wu et al 2009;Merakova and Gvozdik 2009;Bozinovic et al 2011). Hence, there is an increasing awareness of the potential importance of developmental temperature ßuctuation.…”
Section: Discussionmentioning
confidence: 99%